A revision of the genus Malus Mill. (Rosaceae) - Jing-chao Li; Jian-quan Liu; Xin-fen Gao (European Journal of Taxonomy, 2022)
A revision of the wild species in the genus Malus Mill. (Rosaceae) is presented based on numerical analyses and specimens from herbaria around the world, while cultivated species such as Malus domestica (Suckow) Borkh. are not included because of their complicated domestication history. Infra- and interspecific morphological variation and species delimitation are clarified based on Principal Component Analyses (PCA) and Cluster Analyses (UPGMA). We found that several morphological characters traditionally used to distinguish species have limited taxonomic value because of high phenotypic variation or plasticity. There is a substantial conflict between traditional morphological and genetic taxonomic concepts, and as a result species lineages are often morphologically indistinguishable. None of the analyses supports the recognition of infraspecific categories in Malus transitoria (Batalin) C.K.Schneid. and interspecific categories between Malus doumeri (Bois) A.Chev. and Malus leiocalyca S.Z.Huang. Based on our analyses, we recognize 26 wild species in the genus, and propose seven new synonymies.